Lactobacillus Casei Zhang Alleviates Shrimp Tropomyosin‐Induced Food Allergy by Switching Antibody Isotypes through the NF‐κB‐Dependent Immune Tolerance. Issue 10 (5th May 2020) - Fu, Linglin; Xie, Menghua; Wang, Chong; Qian, Yi; Huang, Jianjian; Sun, Zhihong; Zhang, Heping; Wang, Yanbo
Abstract : Scope: Shellfish allergy is an important cause of food allergy, and tropomyosin (TM) is the major allergen within shellfish. Probiotics are safe bacteria that benefit host health and nutrition and is proposed as a novel approach for treating immunological diseases, including food allergies. Methods and results: The probiotic strain Lactobacillus casei Zhang (LcZ) isolated from koumiss is investigated for its capacity to modulate food allergy induced by TM in BALB/c mice. Oral administration of LcZ attenuated allergy symptoms and intestinal epithelial damage. Furthermore, flow cytometry, real‐time quantitative PCR, and ELISA demonstrated that LcZ administration altered the development and function of dendritic cells (DCs), T cells, and B cells, finally resulting in the change of TM‐specific antibody isotypes into a tolerogenic pattern. Moreover, an in vitro spleen cell culture model reveals that LcZ directly modulates regulatory tolerogenic DC and T cell development, dependent on the activation of the nuclear factor kappa B (NF‐κB) signaling pathway. Conclusion: This work indicates the ability of LcZ to alleviate TM‐induced food allergy and demonstrates the involvement of the tolerogenic immune cells and NF‐κB signaling pathway, indicating LcZ to be a potential immunomodulator and immunotherapy assistor. Abstract : Lactobacillus casei Zhang (LcZ) prevents TM‐induced intestinal epithelia instability and the subsequent production of subsequent allergic cytokines to suppress Th2 skewing. LcZ also promotes tolerogenic dendritic cell and regulatory T cells development by activating the nuclear factor kappa B (NF‐κB) signaling pathway. Both effects direct B cells to produce anti‐allergic IgA rather than allergic IgE, finally establishing oral tolerance.